2021
DOI: 10.1017/s0142716421000436
|View full text |Cite
|
Sign up to set email alerts
|

The sentence repetition task as a measure of sign language proficiency

Abstract: Sign language research is important for our understanding of languages in general and for the impact it has on policy and on the lives of deaf people. There is a need for a sign language proficiency measure, to use as a grouping or continuous variable, both in psycholinguistics and in other sign language research. This article describes the development of a Swedish Sign Language Sentence Repetition Test (STS-SRT) and the evidence that supports the validity of the test’s interpretation and use. The STS-SRT was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…The dependent variable was the number of correctly reproduced sentences. As estimates of reliability, internal consistency and inter-rater reliability provided excellent values in a previous study, with Cronbach's α = 0.92 and ICC = 0.90 (Schönström and Hauser, 2021). Furthermore, the test provides evidence for good validity as suggested by better performance in adults than in children, and that delayed language acquisition is associated with lower scores.…”
Section: Swedish Sign Language Sentence Repetition Testmentioning
confidence: 60%
See 1 more Smart Citation
“…The dependent variable was the number of correctly reproduced sentences. As estimates of reliability, internal consistency and inter-rater reliability provided excellent values in a previous study, with Cronbach's α = 0.92 and ICC = 0.90 (Schönström and Hauser, 2021). Furthermore, the test provides evidence for good validity as suggested by better performance in adults than in children, and that delayed language acquisition is associated with lower scores.…”
Section: Swedish Sign Language Sentence Repetition Testmentioning
confidence: 60%
“…To assess sign language sentence reproduction, the Swedish Sign Language Sentence Repetition Test (STS-SRT, Schönström and Hauser, 2021), a Swedish adaptation of the American Sign Language Sentence Repetition Test (ASL-SRT; Hauser et al, 2008), was used. Filmed STS sentences (N = 31), of different length and difficulty, produced by a deaf native signing man, were presented to the participant.…”
Section: Swedish Sign Language Sentence Repetition Testmentioning
confidence: 99%
“…Pilot work using this test with DHH adults showed that even native signers found it challenging to recall all aspects of the sentences, with almost none achieving full marks. The same pattern has also been found in SRTs in other sign languages (Hauser et al, 2008;Schönström & Hauser, 2021). As a result, SRTs developed for DHH adults in ASL (Hauser et al, 2008), BSL (Cormier et al, 2012), German Sign Language (DGS; Kubus & Rathmann, 2012) and Swedish Sign Language (SSL; Schönström & Hauser, 2021) minimize facial expressions when presenting sentences and ignore errors in facial expression when scoring.…”
Section: Sign Language Assessment Instrumentsmentioning
confidence: 61%
“…Another type of test used to measure sign language development involves repetition of linguistic material such as sentence repetition (Haug et al, 2020;Hauser et al, 2008;Schönström & Hauser, 2021). Repetition tests have the advantage of being applicable to a range of ages, and have been used effectively in spoken languages to identify developmental language disorder (DLD) (e.g., Maillart & Parisse, 2008;Snow & Hoefnagel-Höhle, 1978;Stokes & Fletcher, 2003;Volterra et al, 2003).…”
Section: Sign Language Assessment Instrumentsmentioning
confidence: 99%
“…Across all conditions in both studies, age of first language acquisition was a strong predictor of performance. The pattern that emerged from the two initial studies and that has since been replicated with additional controls and alternative protocols ( Mayberry and Eichen, 1991 ; Mayberry, 1993 ; Emmorey et al, 1995b ; Morford and Carlson, 2011 ; Hauser et al, 2016 ; Woll, 2018 ; Schönström and Hauser, 2022 ), is that earlier acquisition is associated with rapid and efficient processing of phonological form in order to access and store linguistic meaning. In Mayberry and Fischer’s studies, native signers deleted or substituted signs during shadowing and recall, but in a manner that preserved the meaning of the stimulus sentences.…”
Section: Introductionmentioning
confidence: 94%